Literasi keagamaan untuk membentuk sikap moderasi - Abidah, Faizah Nurul (Maliki Interdisciplinary Journal, 2026)
This study aims to describe and discover the values ​​of moderation. This descriptive qualitative study comprehensively focuses on the study of the development pattern of religious literacy and its significance in forming a moderate attitude, using data collection methods through interviews, observations, and documentation studies that are analyzed cyclically including the condensation to verification stages. The findings of this study classify the values ​​of moderation into two main categories, namely religious spiritual values ​​that emphasize aspects of balance and humility, and national social values ​​that include the principles of tolerance, justice, openness, and a spirit of patriotism. This is in line with the Religious Moderation program promoted by the Ministry of Religious Affairs and the thoughts of Mohammad Hashim Kamali who emphasizes that the core of Islamic teachings lies in justice and a balance of perspectives to avoid extreme thoughts. In this context, religious literacy—especially in the digital space—is a crucial preventive instrument to reduce the escalation of conflict while increasing the competitiveness of students in the Industry 5.0 era. As emphasized by Diane L. Moore and Masdar Hilmy, an individual's ability to analyze the interaction of religion with socio-political dimensions and the adoption of a rational modern lifestyle are important pillars of a literate society. Therefore, a strategy for developing religious literacy to internalize the value of moderation in the campus environment must be implemented through optimizing digital media, empowering student organizations, increasing reading interest on a large scale, and cultivating a tradition of inclusive critical discussion in socializing with Indonesia's diverse society.